Analysis of the Effect of Average Years of Schooling, Pre-Employment Card Program, and Labor Force Participation Rate on Open Unemployment Rate in 32 Provinces of Indonesia - Br Meliala, Micha Ella; Marseto; Utami, Anisa Fitria (Journal of Macroeconomics and Social Development, 2025)
This research aims to analyze the influence of Average School Length, Pre-Employment Card Program, and Labor Force Participation Rate (TPAK) on the Open Unemployment Rate (TPT) in Indonesia. Open unemployment is one of the main indicators of employment problems, which is influenced by various factors, including education level, access to job training, and participation in the labor market. This research uses a quantitative approach with panel data from 32 provinces in Indonesia during the period of 2020 to 2023. The analysis method used is panel data regression with the Fixed Effect Model (FEM) approach, which is determined through the Chow test and the Hausman test. The results of this study indicate that the average length of schooling and the level of labor force participation have a significant negative effect on the Open Unemployment Rate in 32 provinces of Indonesia. However, this study found that the Pre- Employment Card Program has no effect on Open Unemployment. This research provides new insights into how the government’s role in education and program policies can have a new influence on the Open Unemployment Rate.